Emergency endovascular management of the common femoral artery rupture due to radiotherapy for scrotal carcinoma - Bracale, Umberto Marcello (Acta Radiol Short Rep, 2015)
We describe the case of a 72-year-old man with massive hemorrhage and shock resulting from rupture of the left common femoral artery as a complication of radiotherapy in the groin for cancer of the scrotum. This complication is extremely rare, presents dramatically, and is usually fatal. The patient was successfully treated with a stent graft deployment in order to achieve immediate hemostasis maintaining blood flow to the leg. Open surgery is not ideal in those cases especially when there is extensive tumor involvement of the groin causing altered anatomy and increasing the risk of re-bleeding.